Contact Dynamics and Control for Tethered Space Net Robot - Zhao, Yakun; Huang, Panfeng; Zhang, Fan; Meng, Zhongjie (IEEE transactions on aerospace and electronic systems, 2019)
Maneuverable tethered space net robot (TSNR) is promising for active debris removal due to its flexibility and controllability. However, the contact dynamics of TSNR is not completely understood. Therefore, the contact dynamics is analyzed and the net does not close completely after contact. A super-twisting sliding mode control scheme is designed to make the net completely closed and avoid the risk of tether cut. The efficacy of the controller is validated by simulation results.